2021
DOI: 10.3390/cells10123389
|View full text |Cite
|
Sign up to set email alerts
|

Parkin beyond Parkinson’s Disease—A Functional Meaning of Parkin Downregulation in TDP-43 Proteinopathies

Abstract: Parkin and PINK1 are key regulators of mitophagy, an autophagic pathway for selective elimination of dysfunctional mitochondria. To this date, parkin depletion has been associated with recessive early onset Parkinson’s disease (PD) caused by loss-of-function mutations in the PARK2 gene, while, in sporadic PD, the activity and abundance of this protein can be compromised by stress-related modifications. Intriguingly, research in recent years has shown that parkin depletion is not limited to PD but is also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 188 publications
(272 reference statements)
0
6
0
Order By: Relevance
“…Homozygous mutations in PARK2 and PINK1 are the most known causes of autosomal recessive early onset parkinsonism [ 13 , 34 ]. Furthermore, single heterozygous PARK2 or PINK1 variants are higher in PD patients than controls and have been associated with subclinical parkinsonism [ 35 ]. PARK2 and PINK1 are essential regulators of mitophagy, one of the autophagy pathways for selective removal of dysfunctional mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous mutations in PARK2 and PINK1 are the most known causes of autosomal recessive early onset parkinsonism [ 13 , 34 ]. Furthermore, single heterozygous PARK2 or PINK1 variants are higher in PD patients than controls and have been associated with subclinical parkinsonism [ 35 ]. PARK2 and PINK1 are essential regulators of mitophagy, one of the autophagy pathways for selective removal of dysfunctional mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recent research has shown that parkin depletion is not limited to PD but is also observed in other neurodegenerative diseases, especially those characterized by TDP-43 proteinopathies, such as ALS and frontotemporal lobar degeneration [ 35 ]. In particular, decreased levels of parkin have been found in mouse adult brain, stem-cell-derived human neurons, human fibroblasts, and motor neurons from sporadic ALS patients [ 35 ]. Furthermore, in motor neurons derived from sporadic ALS patients, a correlation has been established between decreased parkin and the presence of TDP-43 aggregates [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a defective process occurs in Parkinson's disease 10 and is due to the mutations of the corresponding genes. Recent reports demonstrate that the recessive early‐onset Parkinson's disease is associated with biallelic mutations in PINK1 43 and the loss‐of‐function mutations in the PARK2 gene, resulting in Parkin depletion 44 . In Parkin‐deficient mice, mutations in the mouse Parkin gene (Park2) are accomplished by the targeted deletion of Parkin exon 2 45 …”
Section: The Mdvs Trafficking Pathwaysmentioning
confidence: 99%
“…Recent reports demonstrate that the recessive early-onset Parkinson's disease is associated with biallelic mutations in PINK1 43 and the loss-of-function mutations in the PARK2 gene, resulting in Parkin depletion. 44 In Parkin-deficient mice, mutations in the mouse Parkin gene (Park2) are accomplished by the targeted deletion of Parkin exon 2. 45 Recent studies uncovered both the proteins beyond the MDVs flux to lysosomes/endo-lysosomal compartment and those required for the fusion between the MDVs (containing oxidized proteins and lipids) and the degradative organelle.…”
Section: Themdvstr Affi Ck Ingpathwaysmentioning
confidence: 99%
“…The E3 ubiquitin ligase Parkin has been reported to ubiquitinate TDP-43 and to facilitate its cytoplasmic accumulation in a multiprotein complex containing HDAC6 ( Hebron et al, 2013 ). Moreover, TDP-43 was shown to regulate Parkin expression, resulting in a decreased abundance of Parkin in motor neurons from ALS patients with TDP-43 pathology, which may contribute to the mitochondrial defects observed in TDP-43 pathologies ( Polymenidou et al, 2011 ; Lagier-Tourenne et al, 2012 ; Gaweda-Walerych et al, 2021 ). The E2 ubiquitin conjugating enzymes UBE2E and the ubiquitin isopeptidase Y (UBPY) were identified as TDP-43-interacting proteins that regulate the ubiquitination of wildtype TDP-43, TDP-43 mutants and C-terminal fragments ( Hans et al, 2014 ).…”
Section: Specific Stress Granule Proteins and Their Regulation By Ubi...mentioning
confidence: 99%